Strategic management accounting and decision making: A survey of the Nigerian Banks - Collins S. Oboh; Solabomi O. Ajibolade (Future Business Journal, 2017)
This paper attempts an empirical examination of the practicality of strategic management accounting (SMA) adoption in banks in Nigeria, a developing country. It investigates the extent of practice and contributions of SMA to strategic decision making. Survey data were obtained from 71 bank managers across 20 registered banks in Nigeria. Simple regression estimation technique and Pearson Chi-square test were used for data analysis. The results suggest that SMA is distinct in its features and orientation towards the practice of management accounting. The study found out that banks in Nigeria practice SMA; not as a concept, but as a principle of operation, and that SMA contributes significantly to strategic decision making in the area of competitive advantage and increased market share. The study offers value for banks in other developing economies in that it supports the argument that they can benefit from SMA adoption as part of banking strategies. Keywords: Strategic management accounting, Decision making, Market share, Banks, Nigeria